2010
DOI: 10.1088/0953-8984/22/8/084006
|View full text |Cite
|
Sign up to set email alerts
|

The role of low-energy electrons in the high-energy radiolysis of condensed CF3I

Abstract: The dynamics of electron-induced reactions in condensed trifluoroiodomethane (CF3I) were studied under ultrahigh vacuum conditions. Seven CF3I radiolysis products (C2F6, C2F5I, C2F3I, CF2I2, C2F4I2, CFI3 and C2F3I3) were identified using temperature-programmed desorption experiments conducted after irradiation with 4 eV electrons. Although C2F6 formation at energies above 4 eV is ascribed to electron-induced electronic excitation followed by prompt dissociation of the C-I bond to form [Formula: see text] radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…There is very little data on Y (E) at these energies with respect to the maximum Y (E) (which is generally between 80 and 200 eV). Based on the available data for CF 3 I, 39 Fe(CO) 5 40 and methyl lactate 41 it is concluded that Y (1 eV, 2 eV) o Y (80-200 eV) . Therefore, a value of Y (E) of 0.5 times the maximum gives a reasonable upper limit for the matrix inversion and enables us to estimate the importance of the SE yield at low PE energies.…”
Section: Resultsmentioning
confidence: 99%
“…There is very little data on Y (E) at these energies with respect to the maximum Y (E) (which is generally between 80 and 200 eV). Based on the available data for CF 3 I, 39 Fe(CO) 5 40 and methyl lactate 41 it is concluded that Y (1 eV, 2 eV) o Y (80-200 eV) . Therefore, a value of Y (E) of 0.5 times the maximum gives a reasonable upper limit for the matrix inversion and enables us to estimate the importance of the SE yield at low PE energies.…”
Section: Resultsmentioning
confidence: 99%